2020
DOI: 10.3389/fpsyg.2020.576402
|View full text |Cite
|
Sign up to set email alerts
|

The Centrality of Events, Religion, Spirituality, and Subjective Well-Being in Latin American Jewish Immigrants in Israel

Abstract: This study aims to explore the impact of migration as a central event in personal identity, spirituality, and religiousness on subjective well-being (SWB). The sample was composed of 204 Latin American immigrants living in Israel, with ages ranging from 18 to 80 years (M = 48.76; SD = 15.36) across both sexes (Men = 34.8%; Women = 65.2%). The results show that, when analyzing the effects on SWB, Positive and Negative Affect, Centrality of Event, Religious Crisis, and Spiritual Transcendence present as the most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 74 publications
(89 reference statements)
1
5
0
1
Order By: Relevance
“…Previous findings also indicate that in stressful times, individuals tend to turn to religion for support, as it is considered a positive force for mental health (Simkin, 2020). This positive correlation is consistent across SWB and religiosity studies.…”
Section: Religion and Subjective Well-beingsupporting
confidence: 74%
See 2 more Smart Citations
“…Previous findings also indicate that in stressful times, individuals tend to turn to religion for support, as it is considered a positive force for mental health (Simkin, 2020). This positive correlation is consistent across SWB and religiosity studies.…”
Section: Religion and Subjective Well-beingsupporting
confidence: 74%
“…COVID-19 has disrupted the lives of many, and religion has become a major coping mechanism (Bentzen, 2019(Bentzen, , 2020Simkin, 2020). Using consumer culture theory, we explored whether religiosity improved SWB among the religious during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the relation between religion and health has been researched for decades with hundreds of qualitative reports, cross-sectional and longitudinal studies, and even randomized controlled trials with religious/spiritual interventions for mental health issues (Captari et al, 2018;Harris et al, 2018;Koenig et al, 2020;Rosmarin et al, 2010). Yet new studies keep emerging (e.g., Chang et al, 2021;Luo & Chen, 2021;Simkin, 2020) and the debate seems far from settled (see for instance the recent special issue in the International Journal for the Psychology of Religion; van Elk, 2021). Second, both 'religion' and 'well-being' are broad and multifaceted constructs that are sensitive to different measures and operationalizations, which might result in both quantitatively and qualitatively different conclusions (Hackney & Sanders, 2003;Poloma & Pendleton, 1989).…”
Section: A Many-analysts Approachmentioning
confidence: 99%
“…The study leaves open to understand where positive affect comes from -probably from the support of your community and the rewarding aspects of the migration experience. Simkin (2020) examines the influence of centrality of migration in the case of Latin American jews that migrates to Israel and found that centrality or subjetive importance of migration was positively related to well being -probably because migration satisfy needs for belongingness, competence and to a lower extent autonomy needs, and is congruent with self-transcendent beliefs or spirituality. Oriol et al (2020) examines the role of self-trascendent prosocial communitarian aspirations, related to intrinsic motivation in the Deci & Ryan approach, as well as to self-trascendent emotions like gratitude.…”
Section: Social Belongingness As a Social Need And As Social Inclusionmentioning
confidence: 99%